Mananjemen Sumber Daya Manusia Di SMP Kartika V-I Balikpapan: Analisis dan Implementasi: MANAJEMEN SUMBER DAYA MANUSIA DI SMP KARTIKA V-I BALIKPAPAN: ANALISIS DAN IMPLEMENTASI - mardatillah mardatillah (STIE Madani Balikpapan, 2026)
Human resource management in the field of education, particularly at the junior high school level, is rarely discussed and lacks analysis regarding the implementation of human resources. This research aims to analyze in depth the human resource management practices applied at SMP Kartika V-I and to evaluate their impact on educational performance. The approach used in this study is a qualitative case study that emphasizes the human resource management case at SMP Kartika V-I Balikpapan. The research findings reveal that SMP Kartika V-I has a clear and well-defined organizational structure, which facilitates communication and efficient decision-making between management and staff. This structure supports sustainable management and ensures that every element within the organization has a clear role. Next is systematic recruitment where the recruitment process at SMP Kartika V-I is conducted transparently and thoroughly, involving various selection stages. Following that is the ongoing training program where the school provides relevant training and development for teachers, helping them stay updated with the latest teaching methods and technology. The result is an improvement in teaching skills and effectiveness in the learning process. Next, the implementation of a reward system and constructive feedback has increased teachers' motivation and performance.